Ontology-based Semantic Representation for Arabic Text: A Survey (Journal of Informatics and Mathematical Sciences, 2017)
The explosion of information available on the Internet motivates researchers to semantically manipulate this information to enable Internet users to find what they actually need easily. One of the important pillars to manipulate data semantically is ontology. Arabic ontology is recently gains a lot of attention. This paper survey some available Arabic ontologies and compares between these ontologies to clarify the difference between the main categories of Arabic ontologies. Ontology creation approach and representation method is considered in this study.
Keywords: semantic web; Arabic ontology; semantic representation; NLP